Low uptake of nasal influenza vaccine in Polish and other ethnic minority children in Edinburgh, Scotland. Issue 5 (29th January 2019) - Bielecki, K.; Kirolos, A.; Willocks, L.J.; Pollock, K.G.; Gorman, D.R.
Highlights: Ethnic minority primary school pupils have lower uptake of seasonal nasal influenza vaccine than White British pupils. Nasal influenza vaccine acceptance in parents of Polish primary school pupils was 25% (70.7% in White British). Polish parents of primary school students were more likely to decline nasal influenza vaccine. Abstract: Failure to vaccinate is well-recognised in Europe as a contributing factor to outbreaks of infectious diseases. Low immunisation rates are often associated with religious, social and ethnic minorities, including refugees or migrant groups. Polish people form Scotland's newest and largest migrant group. They have moved to Scotland since 2004, joining established ethnic minorities from China, the Indian subcontinent and Africa. Scotland has had a seasonal influenza nasal vaccination programme for all primary school children since 2013. We investigated three primary schools in Edinburgh, which had reported low influenza vaccination uptake rates in 2016 and 2017 and found that these schools contained many pupils from ethnic minorities, the majority of whom were Polish. Pupils were categorized as one of three ethnic groupings: White British, Polish and Other Identified Ethnic Minority (OIEM). We ascertained ethnicity using NHS and Education Department information sources and name recognition. We examined vaccine acceptance, declination and non-return of consent forms. In 2017, nasal influenza vaccine uptake was 70.7% (65.2–75.6%, p < 0.001) in White British, 60.9% (53.9–67.6%%, p < 0.001) in other identified ethnic minorities and 25.0% (20.9–29.6%, p > 0.001) in Polish children. White British children were more likely to return completed forms (78.9%) than other groups (OIEM 68.2% and Polish 61.8%). 36.8% of Polish families completed a consent form declining vaccination compared to 6.2% of White British families. These findings demonstrate that significant differences exist in nasal influenza vaccination uptake rates, which have important implications for the trans-national study of vaccine hesitancy. Further qualitative work and an investigation of uptake rates of other childhood immunisations in Polish and other migrant groups is required to assess differences in uptake and behaviours.